Employer Branding in the Context of the Company’s Sustainable Development Strategy from the Perspective of Gender Diversity of Generation Z - Rzemieniak, Magdalena; Wawer, Monika (Sustainability, 2021)
Applying the principles of sustainable development is an element of building the image of an organisation as an employer. The opinions of young people commencing their professional career in this regard may prove important for companies. The aim of this article is to identify a dependence between generation Z’s opinions on employer branding measures based on sustainable development taken by companies and the respondents’ gender. The article presents the results of primary research conducted on a sample of 291 students of higher education institutions in Poland. The methods include questionnaire surveys and statistical data processing. The results of the research suggest that sustainable development measures undertaken by employers increase the candidates’ motivation to apply for a job in the organisation. The analysis demonstrated that generation Z’s opinions on sustainable development activities carried out by employers and on the significance of employer branding are dependent on the respondents’ gender. The main conclusion is that women are more ecologically oriented than men, and following a sustainable development strategy is more important for them. Companies building employer branding should consider the adoption of various factors identified in the article, such as the Employee Value Proposition (EVP), especially when their workforce is gender-diverse.